Answer:
x=4
Step-by-step explanation:
tangent lines from the same point to a circle are congruent in length, so we can say that
5x+8 = 8x-4
5x -5x +8 = 8x - 5x -4
8 = 3x - 4
8+4 = 3x -4 + 4
3x = 12
3x/3 = 12/3
x=4
Answer:
(- 1/2 , √3/2)
Step-by-step explanation:
t=20π/3
t' = 20π/3 - 6π = 2π/3 (120°) ... 2nd quadrant
If we start from (1,0) of unit circle, the coordinate of terminal point (x,y)
OF/OE = - cos 60° = x / 1 = - 1/2
FE/OE = sin 60° = y/1 = √3/2
Answer:
Step-by-step explanation:
The equation Thomas wrote is:
...equation 1
Let us subtract 3x from both sides to get:
We now multiply through by 2 to get:
....equation 2
We can see that equation one and two are equivalent and hence have the same solution.
Therefore Sandra's equation is ![-6x+2y=\frac{3}{2}](https://tex.z-dn.net/?f=-6x%2B2y%3D%5Cfrac%7B3%7D%7B2%7D)
Step-by-step explanation:
![{y}^{2} - 1 = 80](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B2%7D%20%20%20-%201%20%3D%2080)
![{y}^{2} = 81](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B2%7D%20%20%3D%2081)
![y = ±9](https://tex.z-dn.net/?f=y%20%3D%20%C2%B19)
![\frac{y - 4}{4} = 1](https://tex.z-dn.net/?f=%20%5Cfrac%7By%20-%204%7D%7B4%7D%20%20%3D%201)
![y - 4 = 4](https://tex.z-dn.net/?f=y%20-%204%20%3D%204)
![y = 8](https://tex.z-dn.net/?f=y%20%3D%208)
![\frac{10 - 63}{y} = 1](https://tex.z-dn.net/?f=%20%5Cfrac%7B10%20-%2063%7D%7By%7D%20%20%3D%201)
![10 - 63 = y](https://tex.z-dn.net/?f=10%20-%2063%20%3D%20y)
![- 53 = y](https://tex.z-dn.net/?f=%20-%2053%20%3D%20y)